MATH SOLVE

4 months ago

Q:
# what is the simplest form of the expression? ^3 sqrt 750 + ^3 sqrt 2058 - ^3 sqrt 48A) 14 ^3 sqrt 6B) 17.5 ^3 sqrt 6C) 33 ^3 sqrt 6D) 10 ^3 sqrt 6

Accepted Solution

A:

^ 3 sqrt 750 + ^ 3 sqrt 2058 - ^ 3 sqrt 48

Rewriting the expression we have

^ 3 sqrt (6 * x ^ 3) + ^ 3 sqrt (6 * y ^ 3) - ^ 3 sqrt (6 * z ^ 3)

That is, we have the following equations:

6 * x ^ 3 = 750

6 * y ^ 3 = 2058

6 * z ^ 3 = 48

Clearing x, y and z we have:

x = 5

y = 7

z = 2

Then, rewriting the expression

x (^ 3 sqrt (6)) + y (^ 3 sqrt (6)) - z (^ 3 sqrt (6))

Substituting the values

5 (^ 3 sqrt (6)) + 7 (^ 3 sqrt (6 *)) - 2 (^ 3 sqrt (6))

10 (^ 3 sqrt (6))

answer

the simple form of the expression is

D) 10 ^ 3 sqrt 6

Rewriting the expression we have

^ 3 sqrt (6 * x ^ 3) + ^ 3 sqrt (6 * y ^ 3) - ^ 3 sqrt (6 * z ^ 3)

That is, we have the following equations:

6 * x ^ 3 = 750

6 * y ^ 3 = 2058

6 * z ^ 3 = 48

Clearing x, y and z we have:

x = 5

y = 7

z = 2

Then, rewriting the expression

x (^ 3 sqrt (6)) + y (^ 3 sqrt (6)) - z (^ 3 sqrt (6))

Substituting the values

5 (^ 3 sqrt (6)) + 7 (^ 3 sqrt (6 *)) - 2 (^ 3 sqrt (6))

10 (^ 3 sqrt (6))

answer

the simple form of the expression is

D) 10 ^ 3 sqrt 6